Learning to Lead from a Distance: Reflexive Learning during a Pandemic - Högberg, Karin (International Journal of Advanced Corporate Learning (iJAC), 2022)
This paper investigates seven leaders learn to “do” leadership from a distance during 19 months of the COVID-19 pandemic. By following the leaders’ reflexive learning over time, the study sheds light on their assumptions, norms and values and how they questioned these in order to create the “new normal.” Drawing on social constructivism, leadership is viewed here as actions being reproduced in everyday situations in communities. Furthermore, the present study used reflexive learning as theoretical framework. The analysis reveals that the leaders faced many challenges, such as lack of face-to-face communication, and that their learning was a persistent process induced by both internal and external reflexive dialogues. These findings can serve as an inspiration to researchers and managers that seek to understand reflexive learning and leadership during disruptive circumstances and how the context challenges and creates leadership.